Implementation of PMA No. 3 of 1999 in Empowering Sakinah Families in the District Community. Alla Kab. Enrekang - H. Mahmuddin; Sudirman; M. Ali Rusdi; Agus Muchsin; Suarning (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
A The general aim of this research is to find out the culture and traditions in families in the district. Alla Kab. Enrekang, To find out the strategic steps taken by religious affairs in building a sakinah family in the district. Alla Kab. Enrekang, and to find out the implementation of PMA No. 3 of 1999 in Empowering Sakinah Families in the District Community. Alla Kab. Enrekang. This type of research is qualitative research carried out at the Religious Affairs Office (KUA) Kec. Alla Kab. Enrekang. The main instruments of this research are observation, interviews and documentation. Data sources are primary data and secondary data. The research results show that first; Culture and traditions in families in Kec. Alla Kab. Enrekang is a wedding tradition in Alla District, Enrekang Regency as a result of the integration of Islamic culture and local culture, producing local wisdom which contains Islamic values ??as the basis of life for the local community. The main values ??contained in it are the value of kamassangsuranan (brotherhood), the value of taratte' (manners), and the value of majiongan penawa (humbleness). Secondly; Strategic steps taken by religious affairs in building a sakinah family in the district. Alla Kab. Enrekang, namely a) Pre-marital guidance through marriage age and suscatin programs, b) Routine counseling to the community, c) Guidance on religious aspects through taklim assemblies and Friday worship, and third; Implementation of PMA No. 3 of 1999 in Empowering Sakinah Families in the District Community. Alla Kab. Enrekang shows positive results by improving the quality of family life through programs that focus on education, welfare and strengthening family values. This policy has succeeded in fostering harmonious relationships within families and strengthening community participation in social and economic activities, although there are still challenges in terms of adapting programs to specific local needs. Overall, PMA No. 3 of 1999 plays an important role in improving the social structure of families and encouraging the creation of a more stable and prosperous society in the district. Alla Kab. Enrekang.